Impactos econômicos e sociais dos biocombustíveis: a expansão da produção de cana-de-açúcar em minas gerais - Oliveira, Izabel Cristina Carvalho de (2010)
The recent rapid expansion of monoculture of cane sugar, encouraged by the expansion of the biofuels program, is raising questions about its possible social impacts in rural areas. Biofuels are seen as a strategic issue for development by the national government as the country aims to meet the international demand of the product, encouraging trade, via export of domestically produced renewable fuels, especially ethanol. However, what this paper intends to show is that the production of biofuels based on the model of agribusiness (specifically the production of ethanol as a Brazilian export product to meet the growing world market) could threaten food production in the event the motion to replace cultures and may lead to increased land concentration in the country, since such production requires large areas of flat and adjacent to his farm, which may cause the displacement of small-scale production with the lease of the property, thus causing a decrease in rates Occupancy at these sites. The used data extracted from the Municipal Agricultural Survey 2006, 2007 and 2008 Agricultural Censuses and the 1996 and 2006 show that the expansion of monoculture of cane sugar has been detrimental to rural populations, as it affects food production, leads to increased land concentration and decreases the levels of occupation in the field, increasing the vulnerability of local social.